you can use the identitity (a+b)^2-(a-b)^2=4*a*b (eq 1), then (a+b)*(a-b)=4 (eq 2). Thus (a+b)^2-(a-b)^2*(a+b)^2=4*(a*b)(a+b)^2. substitute a*b and (a^2-b^2) (quadratic equation. Thus that is very easy. Now use the identity 2*a= (a+b)+(a-b)=(a+b)+4/(a+b)
Hey sir how can sum of two square number be negative so it should be +4√2 right and hence you will only have one solⁿ which is 2√(√2+1) you still took the square root but still a²+b² = a -ve no: is so hard to comprehend😂
you can use the identitity (a+b)^2-(a-b)^2=4*a*b (eq 1), then (a+b)*(a-b)=4 (eq 2). Thus (a+b)^2-(a-b)^2*(a+b)^2=4*(a*b)(a+b)^2. substitute a*b and (a^2-b^2) (quadratic equation. Thus that is very easy.
Now use the identity 2*a= (a+b)+(a-b)=(a+b)+4/(a+b)
Well explained!
Thank you very much!!
3and 1
Hey sir how can sum of two square number be negative so it should be +4√2 right and hence you will only have one solⁿ which is 2√(√2+1) you still took the square root but still a²+b² = a -ve no: is so hard to comprehend😂
Sir, what if b= 2/ 4 then a^4 - 4a^2 - 4 = 0 then X=a^2 then a= 2sqrt2+2sqrt2. a + b= 2sqrt 2+2sqrt2.
@@charbel3408what do you mean by b=2/4
Я бы никогда не додумался что где то может такое сокращение всплыть
asnwer=2+3=5 isit
Why (x+y)^=x^+y^+2Xy???
Who x^2+y^2=(x+y)^2 ?!
إني خريجه دكتوراه كيمياء وليس رياضيات
Solution th-cam.com/video/L9F4MOg54Ps/w-d-xo.html
Too much nonsense! Should simplify it
Хэллоу😂
Solution th-cam.com/video/L9F4MOg54Ps/w-d-xo.html